Emerging Legal Issues About Organ Transplantation From Forensic Cases Having Brain Death and Their Importance in Terms of Forensic Medicine - Tepehan, Selma; Elmas, İmdat and Özkara, Erdem (The Bulletin of Legal Medicine, 2015)
Objective: Transplantation is very imporlantforpatients probably because it is their last chance to survive. Major sources of organs for transplantation are patients under treatment having brain death. Some of them are forensic cases. This study was conducted to reveal problems with transplantations from forensic cases. Characteristics of the cases and opinions of the parties about the subject were investigated. Materials and Methods: In this retrospective study, data about 810 cases having brain death were obtained from Brain Death Forms completed in Istanbul Local Organ and Tissue Transplantation Coordination Department between 2005 and 2009. Data about opinions of 179 physicians and 279 nurses working in intensive care units of education and research hospitals in Istanbul were collected with a questionnaire. Results: Out of 810 cases, 259 (32%) were forensic cases. Of 273 cases that had brain death and were donors for transplantations, 39.9% were forensic cases. Of 109 forensic cases having brain death, 44 donors (40.4%) and 58 non-donors (38.7%) had traffic accidents and 33 donors (30.2%) and 19 non-donors (12.7%) had gunshot wounds. Permission for transplantation was obtained from the public prosecutor only in 6% of the donors. According to analyses of datafrom the questionnaire, 69.1% of the nurses and 74.1% of the physicians believed that new regulations determining criteria for organ transplantation from forensic cases and eliminating shortcomings of current laws should be adopted. Conclusion: New laws are needed to determine criteria for transplantations from forensic cases and eliminate shortcomings of the current laws. Keywords: Brain death, Forensic case, Organ transplantation, Autopsy.